The Collected Dialogues of Plato - Plato (Bollingen series, 2016)
All the writings of Plato generally considered to be authentic are here presented in the only complete one-volume Plato available in English. The editors set out to choose the contents of this collected edition from the work of the best British and American translators of the last 100 years, ranging from Jowett (1871) to scholars of the present day. The volume contains prefatory notes to each dialogue, by Edith Hamilton; an introductory essay on Plato's philosophy and writings, by Huntington Cairns; and a comprehensive index which seeks, by means of cross references, to assist the reader with the philosophical vocabulary of the different translators.